2007
DOI: 10.1111/j.1365-4632.2006.03138.x
|View full text |Cite
|
Sign up to set email alerts
|

Topical zinc oxide vs. salicylic acid–lactic acid combination in the treatment of warts

Abstract: Topical zinc oxide is an efficacious, painless, and safe therapeutic option for wart treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
29
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 17 publications
1
29
0
2
Order By: Relevance
“…154 In a double-blinded RCT of zinc oxide 20% vs. an SA/lactic acid ointment, 50% of patients achieved clearance in the zinc oxide group compared with 42% in the SA/lactic acid group. 155 It is a simple and safe treatment but has not been compared with placebo.…”
mentioning
confidence: 99%
“…154 In a double-blinded RCT of zinc oxide 20% vs. an SA/lactic acid ointment, 50% of patients achieved clearance in the zinc oxide group compared with 42% in the SA/lactic acid group. 155 It is a simple and safe treatment but has not been compared with placebo.…”
mentioning
confidence: 99%
“…A double blind, randomized control trial of 44 patients determined that twice daily application of 20 % zinc oxide ointment achieved a cure rate of 50 % after 3 months [52]. This was higher than the 42 % cure rate achieved by a salicylic/lactic acid ointment combination [53].…”
Section: Zincmentioning
confidence: 98%
“…Complete clearance of plane warts was seen in 85.7% and 42.8% cases from topical 10% and 5% zinc sulphate solution, respectively, while complete clearance was also seen in 11% and 5% of patients with common warts using 10% and 5% zinc sulphate solution, respectively, which was statistically insignificant. Khattar et al [7] observed that topical 20% zinc oxide was more effective than ointment containing salicylic acid (15%) and lactic acid (15%) for the treatment of warts in a randomized double-blind controlled trial of 44 patients. A complete cure was observed after 3 months in 50% patients with common warts in zinc oxide group as compared to 42% in the other group.…”
Section: Infectionsmentioning
confidence: 99%